Ethical culture and moral identity : how they interact and influence unethical behavior in organizations - Resende, Marília Mesquita (2021)
Tese (doutorado)—Universidade de Brasília, Instituto de Psicologia, Programa de Pós-graduação em Psicologia Social, do Trabalho e das Organizações, 2021.